2000
DOI: 10.1176/appi.ajp.157.7.1101
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Panic-Agoraphobic Spectrum Symptoms on Treatment Response in Patients With Recurrent Major Depression

Abstract: A lifetime burden of panic-agoraphobic spectrum symptoms predicted a poorer response to interpersonal psychotherapy and an 8-week delay in sequential treatment response among women with recurrent depression. These results lend clinical validity to the spectrum construct and highlight the need for alternate psychotherapeutic and pharmacologic strategies to treat depressed patients with panic spectrum features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
83
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 108 publications
(87 citation statements)
references
References 21 publications
4
83
0
Order By: Relevance
“…First, a higher proportion of nonresponders than responders had a comorbid anxiety disorder. This is not unexpected given findings of poorer treatment outcome in depressed patients having a comorbid anxiety disorder (Fava et al, 1997;Frank et al, 2000). The comorbidity difference is not likely to be a critical factor because the difference in asymmetry between responders and nonresponders remained the same when patients having comorbidity were excluded from analyses.…”
Section: Discussionmentioning
confidence: 74%
“…First, a higher proportion of nonresponders than responders had a comorbid anxiety disorder. This is not unexpected given findings of poorer treatment outcome in depressed patients having a comorbid anxiety disorder (Fava et al, 1997;Frank et al, 2000). The comorbidity difference is not likely to be a critical factor because the difference in asymmetry between responders and nonresponders remained the same when patients having comorbidity were excluded from analyses.…”
Section: Discussionmentioning
confidence: 74%
“…In our study sample, rates of comorbid PTSD (66% in ours versus 28% in the perinatal study) and borderline personality disorder (37% in ours; not reported in the perinatal study) accounted for significant variability in depression outcomes. In our sample, 86% of participants had at least one comorbid anxiety disorder (versus 56% in the perinatal sample), which could suppress treatment response (34). Furthermore, depression chronicity in our sample may explain the less robust treatment gains, as was found in a recent meta-analysis of treatments for chronic depression (39).…”
Section: Discussionmentioning
confidence: 97%
“…Possible contributors to incomplete treatment response include predominance of chronic depression (73% of the sample), high rate of comorbid disorders, interpersonal sequelae of extensive trauma exposure, and socioeconomic disadvantage. Comorbid disorders, including PTSD and borderline personality disorder, are associated with worse treatment outcomes (3437). The interpersonal resources of many women were extremely limited and marked by conflictual family relationships, responsibilities of single parenthood, and social isolation.…”
Section: Discussionmentioning
confidence: 99%
“…Interpersonal therapy was not successful in preventing recurrence of depression in MTLD-2 . Anxiety and panic symptoms in particular have been associated with poorer response to interpersonal therapy in midlife depressed patients (Frank et al, 2000), with lower levels of stress sensitivity representing an independent predictor of poor response. Anxious patients may feel particularly overwhelmed by interpersonal stress and may avoid problems instead of actively tackling them.…”
Section: Discussionmentioning
confidence: 99%